Scramjet breaks Mach 7 in NASA test. - Jones, W.D.
NASA is celebrating the successful test of a scramjet on 2004 March 27 in which the engine fired for 11 seconds.
Keywords: Mach 7.; NASA; Pegasus booster rocket; Project Falcon; X-43A.; Hypersonic cruise vehicle; Jet engine; Reusable aircraft; Scramjet technology; Speed of sound; Test flight